Development of Organic Fertilizer from Banana Peel, Egg Shell and Yeast for the Effective Growth of Chili Plant - Ahmad Nordin, Norain; Nur Ain Najwa; Nurul Fatihah; Noor Syazwani (Multidisciplinary Applied Research and Innovation, 2022)
In Malaysia, food waste is the most common type of waste. Organic fertilizer made from food waste can assist Malaysia minimize its food waste production. Banana peel and egg shell were utilised to generate an organic fertiliser in this study. Banana peel is high in biomass fiber, nitrogen, potassium, and phosphorus, all of which are essential components of organic fertilizer. Phosphate and calcium, which become essential for plant growth, are found in egg shells. While yeast contain nutritional, efficient and improve soil in plants. As a result, the performance of organic fertilizer was determined using chilli plant in this study. To determine the efficiency of organic fertilizer and pH value. The growth parameters of chilli plants such as height and total number of leaves were measured. Fourier-Transform Infrared Spectroscopy (FTIR) was used to determine the composition of the soil while the soil pH meters are devices used to measure the acidity or alkalinity of a soil.Hence, the best amount for banana peel, egg shell and yeast is 1.6g, 6g and 1g and the pH value is 7.1.